Effect of Nano TiO2 on Properties of Old Corrugated Paper Recycling Waste Water - Sohil Amiri (Regional Information Center for Science and Technology (RICeST), 2014)
Old corrugated container (OCC) recycling generates large volume of effluent which is heavily loaded with pollutants. Its treatment is very difficult and complicated due to the presence of various pollutants and certain chemical with complicated structure. In this study, the treatment of OCC recycling effluent using nano TiO2 was investigated and the treated effluent parameters such as COD, TDS, TSS, TS, EC and turbidity were measured. Nano TiO2 was applied at 0.5%, 1%, 1.5% of the effluent volume and the pH was adjusted at either 5, 9 or 7.3 (as received from mill). The results showed that the nano TiO2 and pH are effective on all of the parameters and the effect was statistically significant at 99%, but the effect of variables on EC was not measured statistically significant. The effect of pH on all of parameter was statistically significant at 99% expect on EC. Optimum condition was pH=9 and the dosage of  nano TiO2= 0.5% and 1%. At this treatment condition, COD, TDS, TSS, TS and turbidity were reduced by 47.5, 38.7, 98, 70.4, and 97.7 % respectively